Innate Immunity Induced by the Major Allergen Alt a 1 From the Fungus Alternaria Is Dependent Upon Toll-Like Receptors 2/4 in Human Lung Epithelial Cells - Hayes, Tristan; Rumore, Amanda; Howard, Brad; He, Xin; Luo, Mengyao; Wuenschmann, Sabina; Chapman, Martin; Kale, Shiv; Li, Liwu; Kita, Hirohito; Lawrence, Christopher B. (Frontiers in Immunology, 2018)
Allergens are molecules that elicit a hypersensitive inflammatory response in sensitized individuals and are derived from a variety of sources. Alt a 1 is the most clinically important secreted allergen of the ubiquitous fungus, Alternaria. It has been shown to be a major allergen causing IgE-mediated allergic response in the vast majority of Alternaria-sensitized individuals. However, no studies have been conducted in regards to the innate immune eliciting activities of this clinically relevant protein. In this study, recombinant Alt a 1 was produced, purified, labeled, and incubated with BEAS-2B, NHBE, and DHBE human lung epithelial cells. Alt a 1 elicited strong induction of IL-8, MCP-1, and Gro-a/b/g. Using gene-specific siRNAs, blocking antibodies, and chemical inhibitors such as LPS-RS, it was determined that Alt a 1-induced immune responses were dependent upon toll-like receptors (TLRs) 2 and 4, and the adaptor proteins MYD88 and TIRAP. Studies utilizing human embryonic kidney cells engineered to express single receptors on the cell surface such as TLRs, further confirmed that Alt a 1-induced innate immunity is dependent upon TLR4 and to a lesser extent TLR2.